PDI Struggle Party School: Strengthening Political Party Institutions and Increasing the Quality of Party Cadres - Hasto Kristiyanto; Hanief Saha Ghafur; Audrey G. Tangkudung (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The party school is the PDI-P's answer to the defeat of the 2004 general election. Through the party school, the consolidation of cadres is carried out intensely so that every candidate for the party leadership council, regional head and deputy regional head, and members of the legislature is required to attend party schools. The institutionalization of political parties through party schools was carried out simultaneously with the affirmation of the political position of the PDI-P, successively as: the Ideological Party based on Pancasila in 2005; affirmation of party management is identical to managing the state in 2010, and PDI-P as the Pioneer Party in 2015 and 2019. The purposes of this paper are to: 1. analyze the significance of party schools in improving the quality of party cadres. 2 to explain the influence of party schools on party institutionalization and the development of party identity and identity on the basis of party ideology, culture and identity. 3. Explain the influence of party schools in suppressing the tendency to personalize leadership within the party.This writing method uses a qualitative descriptive approach and the writing of this paper uses the literature review method (library research). Through this literature review, it was found that the party school was part of the cadre system built by the PDI-P to forge its cadres to become the best candidate leaders for the community. Party schools involve three party pillars, namely structural, legislative, and executive cadres.